PERAN SEMANTIS DALAM KONSTRUKSI KALIMAT BERPREDIKAT KEPEMILIKAN DALAM BAHASA INGGRIS - Amin Basir (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2019)
Discussion of predicative possession is actually a fairly extensive discussion. The aspects studied in this paper is to discuss what role that appears in predicative possession of the English language that is studied semanticallty. The method used is descriptive qualitative method. The data used in this paper is taken from the British National Corpus (http://www.natcorp.ox.ac.uk/). Data collected contains phrase predicated ownership in the English language with the verb have, own, possess, and belong to. The role that arises in predicative possession in English in have, own, possess, and belong to verbs indicate that the noun phrase occupies the position of the subject and object in the form of animate consisting of humans, animals, and plants and it is also convey inanimate objects consisting of concrete objects and abstract objects. The role occupying the subject/owner (possessor) in active sentences with have, own and possess verbs are benefactive, recipient, experiencer, and maleficiary and those which occupy the object/possessee are neutral, and force. While the active sentence on belong to verbs and passive sentences on own verbs that occupy the subject's role are the opposite, namely neutral, and force. In addition, occupying the object are the roles of benefactive, recipient, experiencer, and maleficiary.